Economic costs of biological invasions in terrestrial ecosystems in Russia - Natalia Kirichenko (NeoBiota, 2021)
Terrestrial ecosystems, owing to the presence of key socio-economic sectors such as agriculture and forestry, may be particularly economically affected by biological invasions. The present study uses a subset of the recently developed database of global economic costs of biological invasions (InvaCost) to quantify the monetary costs of biological invasions in Russia, the largest country in the world that spans two continents. From 2007 up to 2019, invasions costed the Russian economy at least US$ 51.52 billion (RUB 1.38 trillion, n = 94 cost entries), with the vast majority of these costs based on predictions or extrapolations (US$ 50.86 billion; n = 87) and, therefore, not empirically observed. Most cost entries exhibited low geographic resolution, being split between European and Asian parts of Russia (US$ 44.17 billion; n = 72). Just US$ 7.35 billion (n = 22) was attributed to the European part solely and none to the Asian part. Invasion costs were documented for 72 species and particularly insects (37 species). The empirically-observed costs, summing up to US$ 660 million (n = 7), were reported only for four species: two insects Agrilus planipennis Fairmaire and Cydalima perspectalis (Walker) and two plants Ambrosia artemisiifolia L. and Heracleum sosnowskyi Manden. The vast majority of economic costs were related to resource damages and economic losses, with very little reported expenditures on managing invasions in terrestrial ecosystems. In turn, agriculture (US$ 37.42 billion; n = 68) and forestry (US$ 14.0 billion; n = 20) were the most impacted sectors. Overall, we report burgeoning economic costs of invasions in Russia and identify major knowledge gaps, for example, concerning specific habitat types (i.e. aquatic) and management expenditures, as well as for numerous known invasive taxa with no reported economic costs (i.e. vertebrates). Given this massive, largely underestimated economic burden of invasions in Russia, our work is a call for improved reporting of costs nationally and internationally.